1988
DOI: 10.1093/oxfordjournals.eurheartj.a062541
|View full text |Cite
|
Sign up to set email alerts
|

Effects of simvastatin on plasma lipid, lipoprotein and apolipoprotein concentrations in hypercholesterolaemia

Abstract: The effect of 24 weeks of treatment with simvastatin, a new HMG coenzyme A reductase inhibitor (dosages of 20 and 40 mg day-1) on serum lipid, lipoprotein and apolipoprotein A-I and B concentrations as well as safety parameters and subjective side effects were studied in 11 patients with familial (FH) and 10 patients with polygenic hypercholesterolaemia (P-HC). The effects on plasma lipoprotein and apolipoprotein concentrations had already been achieved after four weeks in both groups and then remained during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
16
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 0 publications
4
16
0
Order By: Relevance
“…In our study, we found a larger decrease (45%), even though many of the subjects (19 out of 46) were taking lower doses of simvastatin. The greater fall we observed is in line with recent studies [17,18], confirming that simvastatin appears to be one of the most potent of the HMG-CoA reductase inhibitors [27].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, we found a larger decrease (45%), even though many of the subjects (19 out of 46) were taking lower doses of simvastatin. The greater fall we observed is in line with recent studies [17,18], confirming that simvastatin appears to be one of the most potent of the HMG-CoA reductase inhibitors [27].…”
Section: Discussionsupporting
confidence: 92%
“…We have confirmed that simvastatin induces potentially beneficial changes not only in LDL but in triglycerides and HDL [17][18][19][20][21], ancilliary actions that may play an important role in the clinical effectiveness of this drug. We have also shown that the increase in HDL is due to increases in both HDL 2 and HDL 3.…”
Section: Discussionsupporting
confidence: 64%
“…The lack of increase in apoAl, the major apoprotein of HDL, suggests that the cholesterol content of HDL has increased without an increase in the number of HDL particles. This is consistent with some studies (Mol et al, 1986) but not others in which a small increase in apoAl was reported (Leclercq & Harvengt, 1989;Molgaard et al, 1988). Further studies with larger numbers are required to clarify this point.…”
Section: Discussionsupporting
confidence: 92%
“…The 32% overall reduction in total serum cholesterol is of the same order as that reported in previous uncontrolled studies (Leclercq & Harvengt, 1989;Molgaard et al, 1988) and a placebocontrolled study in familial hypercholesterolaemia (Mol et al, 1986). The trend towards an increase in HDLcholesterol is probably beneficial as regards atherosclerotic risk.…”
Section: Discussionsupporting
confidence: 80%
“…Statins, inhibitors of the 3-hydroxy-3-methyl-glutaryl (HMG)-CoA reductase, are widely used to reduce endogenous cholesterol synthesis and improve hypercholesterolemia (20). HMG-CoA reductase is an upstream enzyme in the mevalonate biosynthetic pathway that catalyzes the conversion of HMG-CoA into mevalonate and then, in a number of steps, into farnesylpyrophosphate (FPP), a precursor of cholesterol (21).…”
mentioning
confidence: 99%